Performance of the transition radiation detector and the timing charge detector in the first flight of the CREAM instrument - S. Coutu; H. S. Ahn; P. Allison; M. G. Bagliesi; J. J. Beatty; BIGONGIARI, GABRIELE; P. Boyle; J. T. Childers; N. B. Conklin; M. A. DuVernois; O. Ganel; J. H. Han; et al. (Tata Inst Fundamental Research, 2005)
During the 2004-2005 season in Antarctica the CREAM (Cosmic Ray Energetics And Mass) experiment had a record breaking flight of nearly 42 days. A major science goal of this instrument is the measurement of secondary nuclei at high energy with a transition radiation detector (TRD) using xenon-filled proportional tubes and charge identification devices comprising plastic scintillator and plastic Cherenkov counters. Accurate and stable performance of the TRD and the charge counters is crucial for the reliable identification of secondary nuclei. The performance of these detectors during the flight is discussed and preliminary data are presented.